The work of love: Great Expectations and the English Bildungsroman. Issue 12 (1st December 2020) - Taft, Matthew
ABSTRACT: In Great Expectations, Charles Dickens uses the form of the Bildungsroman to demonstrate how the aspiration to transcend the world of labour transforms the everyday life of an otherwise nondescript individual. As money transforms social ties, the Bildungsroman naturalises the conflict between a system of social organisation where each generation would step into the shoes of the preceding one and another in which each generation desires to transcend the one before. To describe the novel in these terms is to suggest how Dickens broke from the critical position articulated by Franco Moretti, who would have us understand the English Bildungsroman as a form that aspires to reproduce, with minor adjustments, and stabilise a traditional social hierarchy. By rethinking Great Expectations as negotiating a major rift in the relation between the inner world of the individual and the world of objects, Dickens's disfigurations of the form can be seen to presage the emerging professional ruling class who reconcile upward mobility and love through service to others.